EVALUASI PROGRAM PENDIDIKAN DAN PELATIHAN KEPEMIMPINAN TINGKAT IV DI BALAI DIKLAT KEAGAMAAN MANADO - TULUNG, JEANE MARIE (ACTA DIURNA KOMUNIKASI, 2014)
Evaluation of Education and Leadership Training Level IV was conducted to evaluate: (1) the basis and objectives of Education and Leadership Training Level IV, as well as the feasibility of organizing agencies, (2) clarity of Education and Training participant characteristics, circumstances lecturer, curriculum, facilities and infrastructure, (3) compliance with program curriculum and schedules, learning competencies and Senior Lecturer of Education and Training, (4) the overall assessment of the participant, lecturer and organizer. The approach used in this study is a program evaluation approach using model CIPP (Context, Input, Process, Product). The results showed: (1) grounding the program in line with the applicable legislation. Aim of the program is suitable to improve the competence of Echelon IV, (2) the participant meets the criteria, but still very limited administrative lecturer. Curriculum refers to the guidance, facilities fulfill eligibility standards, (3) compliance program with a curriculum and schedule meets the criteria, (4) the overall results of participants, lecturer and organizer meets the criteria. Keywords:Program Evaluation, CIPP Model, Education and Leadership Training Level IV.